Rancang Bangun Mekanika Pembangkit Listrik Tenaga Gelombang Air Laut Dengan Sistem Pelampung - Roberto Pasaribu; Liliek Soeprijadi; Sewiko Sewiko; Riyan Nata (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
The need for electrical energy by society and industry has encouraged research to build electricity generation from new and renewable energy. The sea is a source of renewable energy, especially ocean wave energy. Mechanics for the design and construction of a floating system ocean wave power plant is a power plant that utilizes ocean wave energy with a two-floating system equipped with various components aimed at producing electric power. The aim of this research is to design and manufacture the mechanics of a sea wave power plant. The techniques used in making mechanical components are welding, cutting, smoothing, drilling and dynamo installation. The results obtained from this research are to design and build a mechanical system to produce ocean wave electricity. As a result of equipment testing in the mechanical systems lab, this wave power generator succeeded in lighting electric lights with an electric current output of around (0.01 – 0.02) Ampere and a voltage of (2.70 – 4.90) Volts with a float height of between (30 – 100) cm.